Crack failure behaviors of Ti–6Al–4V dovetail joints subjected to fretting fatigue and effect of laser shock dimple-textured surface coated with diamond-like carbon film - Zhenhua Zhang; Xuesong Fu; Ziwen Cao; Pengtao Gai; Dasheng Wei; Wenlong Zhou; Yufei Zu; Guoqing Chen (Journal of Materials Research and Technology)
Fretting damage can lead to a reduction in fatigue strength by more than half, due to the increased stress on the fretting surface, which accelerates crack initiation and propagation. Laser shock peening (LSP) technology is an advanced method for protecting against fretting fatigue, which reduces the effective stress on the fretting surface of components by introducing a deeper compressive residual stress field. In this work, LSP was utilized to create regularly arranged dimples on the surface of titanium alloy dovetail joints, and followed by diamond-like carbon (DLC) coating to alter fretting friction. Five surface treatment samples including as-machined, conv-LSP, LSP dimple-textured, DLC, LSP dimple-textured + DLC, were prepared for fretting fatigue tests on dovetail joints. The experimental results showed that the fatigue performance of specimens treated with LSP dimple-textured + DLC is better. Furthermore, it is found that wear debris from fretting surface was discharged into crack source area during fretting fatigue, leading to the formation of a fracture debris area forms in the crack initiation zone. The crack initiation zone displays the protrusion morphology characteristics due to the friction effect induced by contact loads. There is an internal correlation between the size of fracture debris area and surface wear resistance. Fracture debris area and the protrusion morphology vary with surface treatments and applied load. This research further reveals that the variation characteristics of the crack initiation area including the fracture debris area, have a positive influence on observing and analyzing failure behavior of fretting fatigue damage.